Case Report on Caries Assessment Using Intraoral Scanner Compared with Bitewing Radiographs - Siew, Bernard; Enax, Joachim; Meyer, Frederic (European Journal of Dentistry, 2024)
Dental caries remains one of the main reasons patients seeing their dentist. They either show up for preventive measures, diagnostics, or treatment of present caries lesions. To date, diagnostics are performed visually, supported by using bitewing radiographs. While radiographic diagnostics should only be performed on a biannual basis, and some caries process will not be seen with visual diagnostics, there remains a lack in regular checkups. Therefore, different technical applications can be used for regular diagnostics. One of those is the near-infrared imaging (NIRI) technology. In this case report, a patient presented with incipient caries lesions. These lesions were diagnosed visually, radiographically, and using NIRI. After diagnosis of incipient caries lesions, the patient was advised to use a hydroxyapatite toothpaste and a hydroxyapatite gel for the remineralization of the lesions and prevention of caries progression. The patient was followed up for 6 months with regular checkups in between. Visual diagnostics and NIRI were used to detecting the caries progress. After 6 months, bitewing radiographs were used in addition. In this clinical investigation we were able to show for the first time that NIRI and bitewing radiographs are able to detect and follow incipient caries lesions. Additionally, this study highlights that hydroxyapatite-containing oral care products are able to arrest and remineralize the caries process.
Keywords: dental caries; near-infrared light; NIRI; bitewing radiograph; toothpaste; hydroxyapatite; digital dentistry